2022
DOI: 10.3390/metabo12020126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fruit and Vegetables Intake with Biomarkers in Children and Adolescents and Their Level of Validation: A Systematic Review

Abstract: Fruit and vegetables (FV) are part of a healthy diet and should be frequently consumed already at a young age. However, intake of FV is difficult to assess in children and adolescents due to various misreporting aspects. Thus, measurement of dietary biomarkers may be a promising alternative to assess FV intake more objectively at young age. To date, dietary biomarkers have been primarily studied in adults, and research focused on their usefulness in children is scarce. However, clinical studies have revealed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 91 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…A high intake of benzoic acid is associated with an increased production of hippurate, which, in physiological conditions, is excreted in urine [ 77 , 78 ]. A high urinary hippurate concentration has been used in several studies as a biomarker for fruit and vegetable intake, and it is generally associated with a positive outcome [ 79 , 80 ]. A recent study in CKD patients found that a dietary acid load corresponding to a high intake of animal-derived food was inversely associated with hippurate plasma concentration.…”
Section: Proteinsmentioning
confidence: 99%
“…A high intake of benzoic acid is associated with an increased production of hippurate, which, in physiological conditions, is excreted in urine [ 77 , 78 ]. A high urinary hippurate concentration has been used in several studies as a biomarker for fruit and vegetable intake, and it is generally associated with a positive outcome [ 79 , 80 ]. A recent study in CKD patients found that a dietary acid load corresponding to a high intake of animal-derived food was inversely associated with hippurate plasma concentration.…”
Section: Proteinsmentioning
confidence: 99%
“…This could potentially be used to assess compliance in human studies. However, they may not specific enough to be considered BFIs of blueberries within the overall diet of an individual, as there are many other anthocyanin-rich foods containing malvidin glycoside, and hippuric acid is a metabolite found after the consumption of many different types of (poly)­phenols and also part of other endogenous pathways. , In addition, intact anthocyanins are not an optimal biomarker of intake due to their instability and low concentration in biofluids …”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of HA are rather complicated as its levels are increased by dietary habits (fruit and vegetable consumption) and reduced during aging. The urinary excretion of HA is increased with age and age-related diseases, such as cognitive impairments, rheumatic diseases, sarcopenia, and hypomobility, and has been proposed as a potential hallmark of aging, frailty, and age-related diseases [ 35 , 36 ]. There are currently not enough data regarding the HA concentration and kinetics in CKD; its protein binding is reduced to 37% in uremic conditions.…”
Section: Discussionmentioning
confidence: 99%